A critical review on liquid superlubricitive technology for attaining ultra-low friction. (September 2022) - Dhanola, Anil; Khanna, Navneet; Gajrani, Kishor Kumar
Abstract: To mitigate and control friction and wear are the primary goals in tribology for a moving mechanical system. On achieving ultra-low friction and wear, energy efficiency, performance and service life of a mechanical system are greatly extended. Superlubricitive technology is one of the emerging research topics in the field of tribology, and is broadly classified into liquid superlubricity and solid superlubricity. As compared to liquid superlubricity, achieving solid superlubricity might be challenging at macroscopic level and under atmospheric condition as it requires unique atmospheres. In addition to that, researchers have found more potential in liquid superlubricitive technology for industrial applications. In this comprehensive study, a state-of-the-art review on various aspects of superlubricitive technology including recent progress in solid superlubricity to achieve ultra-low friction have been presented. Specific detailed discussion has been carried out on the recent advancements in liquid superlubricitive technology. This study also highlights the challenges associated with liquid superlubricitive technology and frames some suggestions for future investigations in liquid superlubricitive technology. It is hoped that this study will help in enhancing reader's knowledge on superlubricitive technology and will guide researchers in seeking future directions and gaps in this area as well. Highlights: Current progress in various aspects of superlubricity are critically reviewed. Fundamental insights and recent progress of liquid superlubricity and combined solid-liquid superlubricity are discussed. Key lubrication mechanisms and challenges involved with superlubricity are discussed. Perspectives of liquid superlubricity in different industrial applications are summarized. Future works of liquid superlubricity are highlighted.